Correlation between NLR and Ferritin in COVID-19 Patients in ICU Dr. Kariadi Hospital - Monica Monica; Herniah Asti Wulanjani (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
COVID-19 infection is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Diabetes mellitus and heart disease comorbid have high morbidity and mortality. Increased neutrophils to lymphocyte ratio (NLR) and ferritin assist early screening of disease severity, especially in the Intensive Care Unit (ICU). Proving relationship between NLR and ferritin in COVID-19 patients in the ICU. The study was an analytical observational with a cross-sectional approach from July-October 2020 at the Laboratory of Clinical Pathology and Medical Records Dr. Kariadi Hospital Semarang. Pearson correlation method significance p<0.05, r 0.3<r<0.5, because normal normality. NLR and Ferritin mean value was 13.91  and 1675  with positive relationship correlation analysis (p=0.012,r=0.437),there was a correlation between NLR and ferritin in COVID-19 patients in the ICU. Increased NLR of COVID-19 patients due to infiltration of the innate and adaptive immune system in infected tissue,causes decreased circulating lymphocytes and disturbed proliferation caused by increased ferritin as an acute phase reactant protein. The study by Pastora JG,et al,2020,that serum ferritin concentrations were higher in non-survivor. In accordance with this, this increases NLR and ferritin in COVID-19 in the ICU. There is a moderate positive correlation between NLR and ferritin in COVID-19 patients at the ICU, Dr. Kariadi Hospital.